Монети и медалјони со ликот на Гоце Делчев - Coins and Medallions with the Image of Goce Delchev - Nacevski, Ivan (Македонски хералд - Macedonian Herald, 2022)
Numismatics is the science of studying, collecting, and preserving currencies in terms of coins and banknotes. From their appearance in the VII century BC until today, coins are an extremely important tool in the creation and shaping of the iconography and symbolism of a society. It may be said that issuing coins, in order to mark an occasion or event, is a phenomenon as old as the coins themselves. The purpose of this article is to review the current practice of the National Bank of the Republic of Macedonia in issuing appropriate collector coins, with special reference to money and other numismatic objects that bear the image of the Macedonian revolutionary Goce Delchev. In 1978, on the occasion of the 75th anniversary of the Ilinden Uprising and the 75th anniversary of his demise, two gold and one silver medallion with his image were issued. Also the National Bank of the Republic of Macedonia issued in 2003, on the occasion of 100 years of Ilinden, a gold coin with his image. Paranumismatical objects from other organizations will also be considered. Events of special importance for Macedonia, as well as certain numismatic events in the region, also influenced the direction of this article.